Challenges, opportunities, and effects of alternative assessment approaches in teaching practices: a systematic literature review - Sanusi, Najdah; Zulkifli, Hafizhah; Hamzah, Mohd Isa (International Journal of Evaluation and Research in Education (IJERE), 2025)
Alternative assessment, encompassing methods such as portfolios, project-based evaluations, and peer assessments, aligns with 21st-century student-centered learning goals by holistically and authentically evaluating students’ progress. This research applies the systematic review literature method with the preferred reporting items for systematic reviews and meta-analyses (PRISMA) protocol. The study analyzed 47 peer-reviewed articles published between 2019 and 2023, sourced from Web of Science, Scopus, and Education Resource Information Centre (ERIC) databases. The thematic analysis revealed three main themes: i) challenges in implementing alternative assessments, including teacher readiness and assessment skills; ii) opportunities for enhancing creativity and variety in teaching approaches; and iii) positive effects on teachers’ motivation and understanding of student learning. The findings highlight the need for targeted professional development to support teachers in effectively implementing alternative assessments. This review contributes to the growing body of knowledge on innovative assessment practices and their impact on teaching and learning in contemporary educational settings.